Doctors' handovers in hospitals: a literature review. Issue 2 (5th January 2011) - Raduma-Tomàs, Michelle A; Flin, Rhona; Yule, Steven; Williams, David
Abstract : Aim: To review studies on hospital doctors' handovers to identify the methods and main findings. Method: A literature search of electronic databases Medline and Embase (via Ovid) was conducted against a set of inclusion criteria. Results: A total of 32 papers were identified. The most common methods of studying handovers were observations and interviews, which typically focused on the sign-out (ie, handover meeting). This is just one stage of the handover process: pre- and posthandover phases were rarely examined. Although providing useful descriptive information, the studies rarely evaluated the quality of handover practices. While communication is generally recognised as the critical component, there has been little training of this skill. Conclusion: The handover literature does not fully identify where communication failures typically occur or influencing conditions, thus hampering the design of effective handover training and tools. A systematic analysis of all the stages of doctors' handovers is required.